Disinformation in the global South - Madrid-Morales, Dani 1980- (John Wiley & Sons, 2022)
The recent rampant global problem of the rampant spread of disinformation in and through the digital ecosystem can perhaps be traced directly to the technological changes in the realm of media production, circulation and consumption. As media tools have become commonplace and user-friendly, the utopian dream of critical media scholarship that sought to democratize speech seems closer to reality than ever before. Alongside this process, the simultaneous decline of editorial authority of traditional media organizations has led to the rise of practices such as citizen journalism that have provided checks and balances to fill in the gaps in coverage of dominant top-down media institutions. Additionally, as users have gradually appropriated the available tools of media production, they have done so for various subversive ends including a now thriving global culture of parody, satire and critique (Wasserman 2020; Kumar 2015) using existing genres and formats to challenge dominant media texts, institutions and discourses. Often adopting the format of the very texts they seek to critique, parodic texts such as news reports and analysis don't fit the category of misinformation as they openly reveal their fake nature, even if towards the end"--